A vulnerability research framework for the development of early warning systems for floods - Erica Tauzer; Mercy J. Borbor-Cordova; Telmo de la Cuadra; Susana del Granado; Carol Franco-Bellini; Carlos Medina; Jhoyzette Mendoza; Moory M. Romero-Fernandez; Anna M. Stewart-Ibarra (Institute for Advanced Development Studies (INESAD), 2017)
Flood risk is increasing in urban areas due to increased population and urban development, a changing climate, coastal subsidence, and deforestation. To reduce people's exposure to floods, many countries have identified the need for Early Warning Systems for Floods (EWSFs). In the United Nations Climate Change COP15, sixteen of the 21 Latin American countries listed the improvement and establishment of early warning systems as a priority need. In this paper, we present a multi-scalar operational research framework that is being used to investigate EWSFs across three countries in Latin America. This novel framework can be applied to institutions or flood-prone communities, providing a standardized and integrative analysis at local and national levels. By analyzing interventions before, during and after flooding events, this generalizable assessment tool provides decision makers with information to evaluate the resource requirements for improving EWSFs.
Keywords: D63; D81; I31; Q54; 330; Early warning systems; flooding; vulnerability; risk management; Latin America